Fabrication of Freestanding Sheets of Multiwalled Carbon Nanotubes (Buckypapers) for Vanadium Redox Flow Batteries and Effects of Fabrication Variables on Electrochemical Performance. (10th March 2017) - Mustafa, Ibrahim; Lopez, Ivan; Younes, Hammad; Susantyoko, Rahmat Agung; Al-Rub, Rashid Abu; Almheiri, Saif
Abstract: Typically, multiwalled carbon nanotubes (MWCNTs) are drop-casted on the surface of the underlying carbon substrates; the outcome is a randomly distributed MWCNT layers leading to uncontrollable structure and unreproducible results. Additionally, we suspect that the electrochemical response is influenced by the primary carbon-based substrate. Herein, we propose the use of freestanding sheets of MWCNTs (buckypapers, BP electrodes) as electrode materials for vanadium redox flow batteries to directly probe the electrochemical activity of MWCNTs toward VO 2+ /VO2 + and V 2+ /V 3+ redox couples; henceforth, eliminating the need for an underlying carbon substrate. The amount of surfactant and the sonication time used during the fabrication of BP electrodes affect their morphological characteristics and electrochemical performances. Although the electrical conductivity of BP electrodes decreases with increasing surfactant amount and increasing sonication time, the heterogeneous rate constants for both redox couples increase as these fabrication variables are increased, indicating that the performance-limiting process is not electrical conductivity but the number of active sites available for the electrochemical reaction. The standard heterogeneous rate constant of the BP electrode with the highest amount of surfactant is comparable to those of state-of-the-art electrodes. Our promising results call for more research on the potential use of BP electrodes in redox flow batteries.